Clinical Features and Prognostic Analysis of Elderly Patients With Late‐Onset Epilepsy - Jie Hu; Long Wang; Jun‐Cang Wu (Brain and Behavior)
ABSTRACT Purpose: To analysis the basic characteristics, comorbidities and prognosis of elderly patients with Late‐Onset Epilepsy (LOE) in the Eastern Region of Hefei, Anhui. Methods: This study finally selected 304 participants who were enrolled at the Second People's Hospital of Hefei between January 2018 and December 2023. The analysis included baseline characteristics, etiology, seizure types, findings from electroencephalography (EEG) and cranial magnetic resonance imaging, comorbidities, anti‐seizure medication (ASM) regimens, and follow‐up of seizure control outcomes within one year. Continuous variables were presented as mean ± standard deviation (SD) or median (IQR) based on normality. Categorical variables were compared using the chi‐square test with Bonferroni correction for multiple comparisons. Results: According to our study, ischemic cerebral infarction (41.12%) was the main factor for LOE in elderly patients among structural factors. Focal seizure (92.76%) was the main seizure type. The most common comorbidity was ischemic cerebral infarction (88.16%), followed by cerebral hemorrhage (22.37%). During the one year follow‐up, the overall effectiveness of seizure control was 73.03%, and 49.34% patients were seizure‐free. The one‐year treatment efficacy of patients with comorbid psychiatric disorders, cognitive impairment or dementia were significantly lower than that of patients without these comorbidities. In terms of medications, sodium valproate accounted for the most at 86.84%. Conclusion: Structural factors are the main etiology for LOE in elderly patients, with ischemic cerebral infarction accounting for the highest proportion. Focal seizure was the main seizure type. Patients with comorbid psychiatric disorders, cognitive impairment or dementia may have poor one‐year treatment efficacy.